Smuts of Maharashtra - PATIL, M.S. (Indian Phytopathology, 2012)
In the present paper, nine species of smuts belonging to four genera have been presented. Out of these, eight are new species and one is recorded for the first time in India. These are Melanotaenium arundlnellae sp. nov., M. echinochloae sp. nov., M. tuberculatae sp. nov., M. urochloae sp. nov., Sorosporium sehimae sp. nov., S. spondiopogonae sp. nov., S. sulcati sp. nov., Tolyposporium tripogonae sp. novo and Tilletia courtetiana Har. and Patouillard. All species arc graminicolous.